Grain Boundary Engineering for Reversible Zn Anodes in Rechargeable Aqueous Zn-Ion Batteries - Yu-Xuan Liu; Jun-Zhe Wang; Lei Cao; Hao Wang; Zhen-Yu Cheng; Li-Feng Zhou; Tao Du (Metals, 2025)
Rechargeable aqueous zinc-ion batteries (AZIBs) have garnered significant research attention in the energy storage field owing to their inherent safety, cost-effectiveness, and environmental sustainability. Nevertheless, critical challenges associated with zinc anodes—including dendrite formation, hydrogen evolution corrosion, and mechanical degradation—substantially impede their practical implementation. Grain boundary engineering (GBE) emerges as an innovative solution for zinc anode optimization through the precise regulation of grain boundary density, crystallographic orientation, and chemical states in metallic materials. This study comprehensively investigates the fundamental mechanisms and application prospects of GBE in zinc-based anodes, providing pivotal theoretical insights and technical methodologies for designing highly stable electrode architectures. The findings are expected to promote the development of aqueous zinc batteries toward a high energy density and long cycle life.